Revisiting the Hunter diagram with the Geneva Stellar Evolution Code. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Simoniello, R.; Meynet, G.; Ekström, S.; Georgy, C.; Granada, A.
Abstract: We produced a model grid of rotating main and post-main sequence stars with the Geneva Stellar Evolution Code (GENEC). The initial chemical composition is tailored to compare with observations of early OB type stars in the Large Magellanic Cloud (LMC) and the grid covers stellar masses in the range of 7 ≤ M / M ⊙ ≤ 15 and initial velocity between 0 km s −1 ≤ v sin(i) ≤ 300 km s −1 . The model grid has been used to determine the changes in the surface Nitrogen abundances during the star evolution and the results have been compared with observations.